Covered Wire
A coated silver-based wire with a palladium-nickel-gold dual-layer coating addresses flexibility and stability issues, ensuring effective FAB formation and reduced twisting, suitable for microelectronic applications.
Patent Information
- Application Number
- JP2023519880
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-15
- Filing Date
- 2021-08-10
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2041-08-10
AI Technical Summary
Existing silver-based bonding wires face challenges in flexibility, FAB formation in air atmosphere, prevention of flowered bonded balls, and stable looping behavior, along with issues like wire twisting during unwinding.
A coated silver-based wire with a silver core and a dual-layer coating of palladium or nickel (100 nm thick) and gold (1-250 nm thick) is developed, with specific grain size and orientation properties, enhancing flexibility and stability.
The coated wire exhibits improved flexibility, stable FAB formation, reduced wire twisting, and enhanced looping behavior, suitable for microelectronic applications.
Smart Images

Figure 0007603154000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated wire comprising a silver-based wire core and a coating layer superimposed on the surface of the wire core. The present invention further relates to a method for producing such a coated wire.
[0002] The use of bonding wire in electronics and microelectronics applications is a well-known state of the art. Originally, bonding wire was made from gold, but today cheaper materials such as copper, copper alloys, silver and silver alloys are used. Such wires may have a metal coating.
[0003] In terms of wire shapes, the most common are bonding wires with a circular cross section and bonding ribbons with a roughly rectangular cross section. Both types of wire shapes have advantages and are useful for certain applications.
[0004] The object of the present invention is to provide a coated silver-based wire suitable for use in wire bonding applications, which apart from meeting basic requirements such as wire flexibility, feasibility of FAB (free air ball) formation in air atmosphere, and corrosion and oxidation resistance, also excels in preventing flowery bonded balls, preventing wire twisting when unwinding from the spool, and stable looping behavior against wire swaying.
[0005] A contribution to the solution of said object is provided by the subject matter of the claims forming the category. The dependent claims of the claims forming the category represent preferred embodiments of the invention, the subject matter of which also contributes to the solution of the above-mentioned object.
[0006] The present invention relates to a wire comprising a wire core (hereinafter also referred to as "core" for short) having a surface, the wire core having a coating layer superimposed on its surface, the wire core itself being a silver-based wire core, the coating layer being a bilayer consisting of an inner layer of palladium or nickel having a thickness of 1-100 nm and an adjacent outer layer of gold having a thickness of 1-250 nm, and the wire having the following intrinsic properties A1) to A3) (see "Test Methods A and B" below): A1) The average grain size of the crystal grains in the wire core measured in the longitudinal direction is in the range of 0.7 to 1.1 μm; A2) The proportion of twin boundaries measured in the longitudinal direction of the wire is in the range of 5 to 40%; A3) 20-70% of the grains in the wire core are <100> The grains of the wire core are oriented in the direction of the <111> The grains are oriented in the drawing direction, and each percentage is based on the total number of grains oriented parallel to the drawing direction of the wire. 10 shows at least one of the wires.
[0007] The term "intrinsic properties" is used herein with respect to the wires of the present invention. Intrinsic properties refer to properties that a wire has by itself (independent of other factors), whereas extrinsic properties depend on the wire's relationship or interaction with other external factors.
[0008] The wire of the invention is preferably a bonding wire for bonding in microelectronics. It is preferably a monolithic body. In the present invention, the term "bonding wire" includes bonding wires with a circular cross section and a small diameter. The average cross section is, for example, between 50 and 5024 μm 2 , preferably 110 to 2400 μm 2 Therefore, the average diameter is in the range of, for example, 8 to 80 μm, or preferably 12 to 55 μm.
[0009] The average diameter of a wire or wire core, simply stated as diameter, can be obtained by the "sizing method". According to this method, the physical weight of the wire for a specified length is determined. Based on this weight, the diameter of the wire or wire core is calculated using the density of the wire material. The diameter is calculated as the arithmetic mean of five measurements of five sections of a particular wire.
[0010] The wire core is a silver-based wire core, i.e., the wire core is comprised of a silver-based material in the form of (a) doped silver, (b) a silver alloy, or (c) a doped silver alloy.
[0011] The term "doped silver" as used herein means a silver-based material consisting of (a1) silver in an amount ranging from >99.49 to 99.997% by weight, (a2) at least one doping element other than silver in a total amount ranging from 30 to <5000 ppm by weight, and (a3) further components (components other than silver and the at least one doping element) in a total amount ranging from 0 to 100 ppm by weight. In a preferred embodiment, the term "doped silver" as used herein means doped silver consisting of (a1) silver in an amount ranging from >99.49 to 99.997% by weight, (a2) at least one doping element selected from the group consisting of calcium, nickel, platinum, palladium, gold, copper, rhodium and ruthenium in a total amount ranging from 30 to <5000 ppm by weight, and (a3) further components (components other than silver, calcium, nickel, platinum, palladium, gold, copper, rhodium and ruthenium) in a total amount ranging from 0 to 100 ppm by weight.
[0012] The term "silver alloy" as used herein means a silver-based material consisting of (b1) silver in an amount ranging from 89.99 to 99.5 wt.%, preferably 97.99 to 99.5 wt.%, (b2) at least one alloying element in a total amount ranging from 0.5 to 10 wt.%, preferably 0.5 to 2 wt.%, and (b3) further components (components other than silver and the at least one alloying element) in a total amount ranging from 0 to 100 ppm by weight. In a preferred embodiment, the term "silver alloy" as used herein means a silver alloy consisting of (b1) silver in an amount ranging from 89.99 to 99.5 wt.%, preferably 97.99 to 99.5 wt.%, (b2) at least one alloying element selected from the group consisting of nickel, platinum, palladium, gold, copper, rhodium and ruthenium in a total amount ranging from 0.5 to 10 wt.%, preferably 0.5 to 2 wt.%, and (b3) further components (components other than silver, nickel, platinum, palladium, gold, copper, rhodium and ruthenium) in a total amount ranging from 0 to 100 ppm by weight.
[0013] The term "doped silver alloy" as used herein means a silver-based material consisting of (c1) silver in an amount in the range of >89.49-99.497 wt.-%, preferably 97.49-99.497 wt.-%, (c2) at least one doping element in a total amount of 30 to <5000 ppm by weight, (c3) at least one alloying element in a total amount in the range of 0.5-10 wt.-%, preferably 0.5-2 wt.-%, and (c4) further components (components other than silver, the at least one doping element and the at least one alloying element) in a total amount of 0 to 100 ppm by weight, wherein the at least one doping element (c2) is other than the at least one alloying element (c3). In a preferred embodiment, the term "doped silver alloy" as used herein means a doped silver alloy consisting of: (c1) silver in an amount in the range of >89.49-99.497 wt.-%, preferably 97.49-99.497 wt.-%, (c2) at least one doping element selected from the group consisting of calcium, nickel, platinum, palladium, gold, copper, rhodium and ruthenium in a total amount of 30 to <5000 ppm by weight, (c3) at least one alloying element selected from the group consisting of nickel, platinum, palladium, gold, copper, rhodium and ruthenium in a total amount in the range of 0.5-10 wt.-%, preferably 0.5-2 wt.-%, and (c4) further components (components other than silver, calcium, nickel, platinum, palladium, gold, copper, rhodium and ruthenium) in a total amount of 0 to 100 ppm by weight, wherein the at least one doping element (c2) is other than the at least one alloying element (c3).
[0014] The disclosure refers to "further components" and "doping elements." The individual amount of any further components is less than 30 ppm by weight. The individual amount of any doping elements is at least 30 ppm by weight. All amounts expressed in weight percent and weight ppm are based on the total weight of the core or its precursor or elongated precursor member.
[0015] The core of the wire of the invention may contain so-called further components in a total amount ranging from 0 to 100 ppm by weight, for example from 10 to 100 ppm by weight. In the present context, further components, often also called "unavoidable impurities", are trace amounts of chemical elements and / or compounds originating from impurities present in the raw materials used or from the wire core manufacturing process. A low total amount of further components of 0 to 100 ppm by weight ensures good reproducibility of the wire properties. The further components present in the core are usually not added separately. Each individual further component is contained in an amount of less than 30 ppm by weight, based on the total weight of the wire core.
[0016] The core of the wire is a homogeneous region of the bulk material. Since in any bulk material there are always surface regions that may exhibit somewhat different properties, the properties of the core of the wire are understood as properties of the homogeneous region of the bulk material. The surface of the bulk material region may differ with respect to morphology, composition (e.g. sulfur, chlorine and / or oxygen content) and other features. The surface is the interface region between the wire core and the coating layer superimposed on the wire core. Typically, the coating layer is completely superimposed on the surface of the wire core. In the region of the wire between the core of the wire and the coating layer superimposed thereon, a combination of both core and coating material may be present.
[0017] The coating layer superposed on the surface of the wire core is a bilayer consisting of an inner layer of palladium or nickel 1-100 nm thick, preferably 1-30 nm thick, and an adjacent outer layer of gold 1-250 nm thick, preferably 20-200 nm thick. In this context, the term "thick" or "thickness of the coating layer" refers to the size of the coating layer in a direction perpendicular to the longitudinal axis of the core.
[0018] The wire of the present invention has the following inherent properties A1) to A3): A1) The average grain size of the crystal grains in the wire core measured in the longitudinal direction is in the range of 0.7 to 1.1 μm; A2) The ratio of twin boundaries measured in the longitudinal direction of the wire is in the range of 5 to 40%, preferably 10 to 40%; A3) 20 to 70%, preferably 30 to 70%, and most preferably 30 to 60% of the crystal grains of the wire core <100> In the direction, 3 to 40%, preferably 3 to 30%, and most preferably 5 to 20% of the crystal grains of the wire core are oriented in the direction. <111> The grains are oriented in the drawing direction, and each percentage is based on the total number of grains oriented parallel to the drawing direction of the wire. At least one of the following is shown.
[0019] The wire of the present invention preferably exhibits at least two of the inherent properties A1) to A3), and more preferably exhibits all of the inherent properties A1) to A3).
[0020] In an advantageous embodiment, the gold layer comprises at least one element selected from the group consisting of antimony, bismuth, arsenic and tellurium in a total proportion ranging from 10 to 300 ppm by weight, preferably from 10 to 150 ppm by weight, based on the weight of the wire of the invention. At the same time, in one embodiment, the total proportion of at least one element selected from the group consisting of antimony, bismuth, arsenic and tellurium can range from 300 to 9500 ppm by weight, preferably from 300 to 5000 ppm by weight, most preferably from 600 to 3000 ppm by weight, based on the weight of gold of the gold layer.
[0021] In an advantageous embodiment, it is preferred that antimony is present in the gold layer, and it is even more preferred that antimony is present alone in the gold layer, i.e. that bismuth, arsenic and tellurium are not present at the same time. In other words, in the most preferred variant of the advantageous embodiment, the gold layer contains antimony in a proportion ranging from 10 to 300 ppm by weight, preferably 10 to 150 ppm by weight, based on the weight of the wire (wire core + coating layer), without the presence of bismuth, arsenic and tellurium in the gold layer, and at the same time, in one embodiment, the proportion of antimony can be in the range of 300 to 9500 ppm by weight, preferably 300 to 5000 ppm by weight, most preferably 600 to 3000 ppm by weight, based on the weight of gold in the gold layer.
[0022] In one embodiment, at least one element selected from the group consisting of antimony, bismuth, arsenic and tellurium may exhibit a concentration gradient within the gold layer, the gradient increasing in a direction towards the wire core, i.e., perpendicular to the longitudinal axis of the wire core.
[0023] In another aspect, the present invention also relates to a method for producing a coated wire of the present invention in any of its embodiments disclosed above. The method includes at least steps (1) to (5): (1) preparing a silver-based precursor material; (2) elongating the precursor member until an intermediate diameter in the range of 30 to 200 μm is obtained to form an elongated precursor member; (3) applying a bilayer coating of an inner layer of palladium or nickel and an adjacent outer layer of gold onto the surface of the elongated precursor member obtained after completion of process step (2); (4) further stretching the coated precursor element obtained after completing process step (3) until a desired final diameter is obtained and a bilayer is obtained consisting of an inner layer of palladium or nickel having a desired final thickness in the range of 1 to 100 nm and an adjacent outer layer of gold having a desired final thickness in the range of 1 to 250 nm; (5) Finally, strand annealing the coated precursor obtained after completion of process step (4) at an oven set temperature in the range of >400-460° C. for an exposure time in the range of ≧0.8-10 seconds, preferably ≧0.8-2 seconds, to form a coated wire. Including, Step (2) may include one or more substeps of intermediate batch annealing the precursor component at an oven set temperature of 200-650°C for an exposure time in the range of 30-300 minutes, preferably at an oven set temperature of 300-500°C for an exposure time in the range of 60-180 minutes.
[0024] The term "strand annealing" is used herein. It is a continuous process that allows high speed production of highly reproducible wire. In the context of the present invention, strand annealing means that the annealing is performed dynamically while the coated precursor to be annealed is pulled or moved through a conventional annealing oven and wound on a reel after exiting the annealing oven. Here, the annealing oven is typically in the form of a cylindrical tube of a given length. The annealing time / oven temperature parameters can be defined and set with their defined temperature profile at a given annealing speed, which can be selected in the range of, for example, 10 to 60 meters / min.
[0025] The term "oven set temperature" is used herein. It means the temperature fixed in the temperature controller of the annealing oven. The annealing oven can be a chamber furnace type oven (for batch annealing) or a tubular annealing oven (for strand annealing).
[0026] The present disclosure distinguishes between precursor member, elongated precursor member, coated precursor member, coated precursor and coated wire. The term "precursor member" is used for a wire pre-stage that has not reached the desired final diameter of the wire core, while the term "precursor" is used for a wire pre-stage of the desired final diameter. After completion of process step (5), i.e. after final strand annealing of the coated precursor of the desired final diameter, a coated wire in the sense of the present invention is obtained.
[0027] The precursor member provided in step (1) is a silver-based precursor member, i.e., the precursor member is comprised of (a) doped silver, (b) a silver alloy, or (c) a doped silver alloy. See the above disclosure for the meaning of the terms "doped silver", "silver alloy" and "doped silver alloy".
[0028] In the embodiment of the silver-based precursor member, the latter can be obtained by alloying, doping, or alloying and doping silver with the required components in the desired amounts. The doped silver or silver alloys or doped silver alloys can be prepared by conventional processes known to those skilled in the art of metal alloys, for example by melting the components together in the desired proportional ratio. In so doing, it is possible to use one or more conventional master alloys. The melting process can be carried out, for example, with the aid of an induction furnace, and is conveniently carried out under vacuum or in an inert gas atmosphere. The materials used can have a purity grade of, for example, 99.99% by weight or higher. The melt thus produced can be cooled to form a homogenous piece of silver-based precursor member. Typically, such precursor members are in the form of rods having a diameter of, for example, 2 to 25 mm and a length of, for example, 2 to 100 m. Such rods can be made by continuous casting of the silver-based melt using a suitable mold, followed by cooling and solidification.
[0029] In process step (2), the silver-based precursor member is stretched to form an elongated precursor member until an intermediate diameter in the range of 30-200 μm is obtained. Techniques for stretching the precursor member are known and are considered useful in the context of the present invention. Preferred techniques include rolling, swaging, die drawing, etc., of which die drawing is particularly preferred. In the latter case, the precursor member is drawn in several process steps until the desired intermediate cross section or desired intermediate diameter is reached. Such wire die drawing processes are well known to those skilled in the art. Conventional tungsten carbide and diamond drawing dies can be used, and conventional drawing lubricants can be used to support the drawing.
[0030] Step (2) of the method of the present invention may include one or more substeps of intermediate batch annealing the elongated precursor member at an oven set point ranging from 200 to 650° C. for an exposure time ranging from 30 to 300 minutes, preferably at an oven set point ranging from 300 to 500° C. for an exposure time ranging from 60 to 180 minutes. Such optional intermediate batch annealing may be performed, for example, by drawing the rod to a diameter of 2 mm and coiling it on a drum.
[0031] The optional intermediate batch annealing of process step (2) may be carried out under an inert or reducing atmosphere. Many types of inert and reducing atmospheres are known in the art and are used to purge the annealing oven. Of the known inert atmospheres, nitrogen or argon are preferred. Of the known reducing atmospheres, hydrogen is preferred. Another preferred reducing atmosphere is a mixture of hydrogen and nitrogen. A preferred mixture of hydrogen and nitrogen is 90-98% by volume nitrogen and correspondingly 2-10% by volume hydrogen, the volume percentages totaling 100% by volume. Preferred mixtures of nitrogen / hydrogen are equal to 93 / 7, 95 / 5 and 97 / 3 vol% / vol%, respectively, based on the total volume of the mixture.
[0032] In process step (3), a coating in the form of a bilayer coating of an inner layer of palladium or nickel and an adjacent outer layer of gold is applied onto the surface of the elongated precursor member obtained after completion of process step (2), overlying the coating on said surface.
[0033] The skilled person knows how to calculate the thickness of such a coating on the elongated precursor member in order to finally obtain a coating with the layer thickness disclosed for the wire embodiment, i.e. after the coated precursor member is finally elongated. The skilled person knows a number of techniques for forming a coating layer of material according to the embodiments on a silver-based surface. Preferred techniques are plating, such as electroplating and electroless plating, sputtering, ion plating, deposition of material from the gas phase, such as vacuum evaporation and physical vapor deposition, and deposition of material from the melt. When applying said bilayer consisting of an inner palladium or nickel layer and an outer gold layer, it is preferred to apply the palladium or nickel layer by electroplating.
[0034] The gold layer is also preferably applied by electroplating. Gold electroplating is carried out with the aid of a gold electroplating bath, i.e. an electroplating bath that allows a palladium or nickel cathode surface to be electroplated with gold. In other words, a gold electroplating bath is a composition that allows gold to be applied directly in elemental metallic form onto a palladium or nickel surface wired as a cathode.
[0035] The electroplating application of the gold layer is carried out by directing the palladium or nickel coated elongated precursor member wired as a cathode through a gold electroplating bath. The gold coated precursor member thus obtained, exiting the gold electroplating bath, may be rinsed and dried before carrying out process step (4). It is expedient to use water as rinsing medium, alcohol and alcohol / water mixtures being further examples of rinsing media. The gold electroplating of the palladium or nickel coated elongated precursor member passing through the gold electroplating bath can be carried out, for example, at a direct voltage in the range of 0.2 to 20 V and at a current in the range of, for example, 0.001 to 5 A, in particular 0.001 to 1 A or 0.001 to 0.2 A. Typical contact times may, for example, be in the range of 0.1 to 30 seconds, preferably 2 to 8 seconds. The current densities used in this connection are, for example, 0.01 to 150 A / dm 2 The gold electroplating bath may have a temperature in the range of, for example, 45 to 75°C, preferably 55 to 65°C.
[0036] The thickness of the gold coating layer can be adjusted as desired essentially by the following parameters: chemical composition of the gold electroplating bath, contact time of the elongated precursor member with the gold electroplating bath, and current density. In this regard, the thickness of the gold layer can generally be increased by increasing the concentration of gold in the gold electroplating bath, by increasing the contact time of the elongated precursor member wired as a cathode with the gold electroplating bath, and by increasing the current density.
[0037] In one embodiment, the method of the present invention is a method of manufacturing the coated wire of the present invention in the advantageous embodiment disclosed above. Here, the application of the gold layer in step (3) is performed by electroplating the gold layer from a gold electroplating bath containing gold and at least one element selected from the group consisting of antimony, bismuth, arsenic and tellurium. Thus, in this embodiment, the gold electroplating bath is a composition that allows not only the deposition of elemental gold, but also the deposition of the at least one element selected from the group consisting of antimony, bismuth, arsenic and tellurium in the gold layer. It is unclear what chemical species the at least one element is, i.e., whether the element is present in the gold layer in elemental form or as a compound. In this embodiment, the gold electroplating bath can be made by adding the appropriate chemical form of the at least one element (e.g., a compound such as Sb2O3, BiPO4, As2O3 or TeO2) to an aqueous composition containing gold as one or more dissolved salts. Examples of such aqueous compositions to which at least one component can be added are Aurocor® K24HF from Atotech, and Auruna® 558 and Auruna® 559 from Umicore. Alternatively, gold electroplating baths can be used that already contain at least one component selected from the group consisting of antimony, bismuth, arsenic and tellurium, for example gold electroplating baths based on MetGold Pure ATF from Metalor. The concentration of gold in the gold electroplating bath can be, for example, in the range of 8 to 40 g / L (grams per liter), preferably 10 to 20 g / L. The concentration of at least one component selected from the group consisting of antimony, bismuth, arsenic and tellurium in the gold electroplating bath can be, for example, in the range of 15 to 50 ppm by weight, preferably 15 to 35 ppm by weight.
[0038] In process step (4), the coated precursor member obtained after completing process step (3) is further stretched (4) until the desired final diameter of the wire is obtained, having a bilayer consisting of an inner layer of palladium or nickel having a desired final thickness in the range of 1-100 nm, preferably 1-30 nm, and an adjacent outer layer of gold having a desired final thickness in the range of 1-250 nm, preferably 20-200 nm. The technique for stretching the coated precursor member is the same stretching technique as described above in the disclosure of process step (2).
[0039] In process step (5), the coated precursor obtained after completion of process step (4) is finally strand annealed at an oven set temperature in the range of >400-460°C for an exposure time in the range of ≥0.8-10 seconds, preferably ≥0.8-2 seconds to form a coated wire.
[0040] In a preferred embodiment, the final strand annealed coated precursor, i.e., the still hot coated wire, is quenched in water, which in one embodiment may contain one or more additives, e.g., 0.01-0.2 vol. % of additives. Quenching in water means immediately or rapidly, i.e., within 0.2-0.6 seconds, cooling the final strand annealed coated precursor from the temperature experienced in step (5) to room temperature, e.g., by immersion or dripping.
[0041] After completion of process step (5) and optional quenching, the coated wire of the present invention is finished. To fully utilize its properties, it is advantageous to use it for wire bonding applications immediately, i.e. without delay, e.g. within 25-70 days, preferably within 60 days after completion of process step (5). Alternatively, to maintain the wide wire bonding process window properties of the wire and to prevent oxidation / sulfidation or other chemical attack, the finished wire is typically wound and vacuum sealed immediately after completion of process step (5), i.e. without delay, e.g. within <1-5 hours after completion of process step (5), and then stored for further use as bonding wire. Storage under vacuum seal should not exceed 12 months. After opening the vacuum seal, the wire should be used for wire bonding within 25-70 days, preferably within 60 days.
[0042] All process steps (1) to (5) as well as winding and vacuum sealing are preferably carried out under clean room conditions (US FED STD 209E clean room standard, 1k standard).
[0043] A third aspect of the present invention is a coated wire obtainable by the above disclosed method according to any embodiment thereof. The coated wire of the present invention has been found to be well suited for use as a bonding wire in wire bonding applications. Wire bonding techniques are well known to those skilled in the art. During wire bonding, a ball bond (first bond) and a stitch bond (second bond, wedge bond) are typically formed. During bond formation, a certain force (usually measured in grams) is applied, which is supported by the application of ultrasonic energy (usually measured in mA). The wire of the present invention exhibits a fairly wide wire bonding process window.
[0044] The present invention is illustrated by the following non-limiting examples, which are intended to be illustrative of the invention and are not intended to limit the scope of the invention or the claims.
[0045] Test Method All tests and measurements were performed at T=20° C. and relative humidity RH=50%.
[0046] A. Electron Backscatter Diffraction (EBSD) pattern analysis to determine the crystallographic orientation of grains and twin boundaries of the wire core: The main steps taken to measure the wire texture were sample preparation, obtaining a good Kikuchi pattern, and calculating the components.
[0047] The wires were first potted using epoxy resin and polished by standard metallographic techniques. Ion milling was applied in the final sample preparation step to remove any mechanical deformation, contamination and oxide layer on the wire surface. The ion milled cross-section sample surface was sputtered with gold. Ion milling and gold sputtering were then performed two more times. No chemical or ion etching was performed.
[0048] The sample was loaded into a FESEM (field emission scanning electron microscope) with the holder angled at 70° to the normal FESEM sample holding table surface. The FESEM was further equipped with an EBSD detector. Electron backscattering patterns (EBSPs) containing the crystallographic information of the wires were obtained.
[0049] These patterns were further analyzed (using software developed by Oxford Instruments called EBSD program) for grain orientation, average grain size, etc. Points with similar orientation were grouped together to form texture components.
[0050] A maximum allowable angle of 10° was used to distinguish between the different texture components. The wire drawing direction was taken as the reference orientation. <100> and <111> The percentage of the texture that is oriented parallel to the reference orientation <100> and <111> It was calculated by measuring the percentage of crystals that have faces.
[0051] The calculation of the average grain size excluded twin boundaries (also called Σ3CSL twin boundaries). Twin boundaries are the boundary between adjacent crystallographic domains with different orientations. <111> The area of interest was described by rotating 60° around the plane. The number of scanning points in the region of interest depended on the step size and was less than one-fifth of the finest grain size observed (approximately 100 nm).
[0052] EBSD pattern analysis was performed at five different locations per sample, and the average value of the five different locations is reported.
[0053] B. Linear intercept method for determining grain size: The wires were first potted using cold mount epoxy resin and then polished (cross sectioned) by standard metallographic techniques. A MultiPrep semi-automatic polisher was used at low force and optimal speed to grind and polish the samples with minimal deformation strain on the sample surface. Finally, the polished samples were chemically etched using ferric chloride to expose the grain boundaries. Grain size was measured using the linear intercept method under an optical microscope at 1000x magnification according to ASTM E112-12 standard.
[0054] C. Evaluation of flower-shaped joint balls: C.1) Preparation of FAB: The procedure described in the KNS Process User Guide for FAB (Kulicke & Soffa Industries Inc, Fort Washington, PA, USA, 2002, 31 May 2009) was followed and worked in ambient atmosphere. The FAB was prepared by performing a conventional electric flame-off (EFO) bake with standard firing (single step, 17.5 μm wire, EFO current 50 mA, EFO time 125 μs). C.2) Ball Bonding: The formed FAB was lowered from a predefined height (tip 203.2 μm) and speed (contact speed 6.4 μm / sec) towards an Al-0.5 wt% Cu bond pad. Upon contact with the bond pad, a set of defined bonding parameters (100 g bond force, 95 mA ultrasonic energy, and 15 ms bond time) were applied to deform the FAB and form a bonded ball. After the ball was formed, the capillary was raised to a predefined height (kink height 152.4 μm, loop height 254 μm) to form a loop. After the loop was formed, the capillary was lowered onto the lead to form a stitch. After the stitch was formed, the capillary was raised and the wire clamp was closed to cut the wire and create a predefined tail length (extended tail length of 254 μm). For each sample, a significant number of 2500 bonded wires were optically inspected using a microscope at 1000x magnification. The percentage of defects was determined. C.3) Evaluation of joint balls against flower joint balls: + Defective: 15% or more of the bonded balls are out of round and deformed. ++Good: 10% to 15% of the bonded balls are out of round and deformed +++Very good: Less than 10% of bonded balls are out of round and deformed C.4) Wire sway evaluation: ++Good: Less than 5% of wires deflect towards adjacent wires in the loop +++Excellent: No loop deflection in wire
[0055] D. Wire twist rating: ++Good: The wire wraps around the coil less than 5 times as it falls freely from the spool during unwinding +++Very good: Wire does not wrap around the coil as it falls freely from the spool during unwinding
[0056] Wire Examples Amounts of 98.5 wt.% silver (Ag) and 1.5 wt.% palladium (Pd) of at least 99.99% purity ("4N") for each metal were melted in a crucible. Wire core precursors in the form of 8 mm rods were then continuously cast from the melt. The rods were then drawn in several drawing passes to form wire core precursors with a circular cross section of 2 mm diameter. The wire core precursors were intermediate batch annealed at an oven set temperature of 500°C for an exposure time of 60 minutes. The rods were further drawn in several drawing passes to form wire core precursors with a diameter of 46 μm.
[0057] The wire-core precursor was electroplated with a double layer coating of an inner layer of nickel and an adjacent outer layer of gold. For this purpose, the wire-core precursor, wired as a cathode, was passed through a hot nickel electroplating bath at 60° C., followed by a hot gold electroplating bath at 61° C. The nickel electroplating bath contained 90 g / L (grams per liter) Ni(SO3NH2)2, 6 g / L NiCl2, and 35 g / L H3BO3, while the gold electroplating bath (based on MetGold Pure ATF from Metalor) had a gold content of 13.2 g / L and an antimony content of 20 ppm by weight (based on MetGold Pure ATF from Metalor).
[0058] The coated wire precursor was then further drawn to a final diameter of 20 μm, followed by a final strand anneal for an exposure time of 0.9 seconds at the oven setpoint temperature shown in Table 1, immediately followed by quenching the so-obtained coated wire in water containing 0.07% by volume of a surfactant. The 20 μm thick wire had an inner layer of nickel 9 nm thick and an adjacent outer layer of gold 90 nm thick.
[0059] [Table 1]
Claims
1. 1. A wire comprising a wire core having a surface, the wire core having a coating layer overlaid on its surface; The wire core itself is a silver-based wire core; the coating layer is a bilayer consisting of an inner layer of palladium or nickel having a thickness of 1-100 nm and an adjacent outer layer of gold having a thickness of 1-250 nm; The wire has the following specific properties A1) to A3): A1) The average grain size of the crystal grains in the wire core measured in the longitudinal direction is in the range of 0.7 to 1.1 μm; A2) The proportion of twin boundaries measured in the longitudinal direction of the wire is in the range of 5 to 40%; A3) 20-70% of the grains of the wire core are oriented in the <100> direction and 3-40% of the grains of the wire core are oriented in the <111> direction, each percentage being relative to the total number of grains oriented parallel to the drawing direction of the wire.
4. A wire indicative of at least one of:
2. 50 to 5024 μm 2 2. The wire of claim 1 having an average cross-sectional area in the range of
3. 2. The wire of claim 1 having an average diameter in the range of 8 to 80 μm.
4. A wire according to any one of claims 1 to 3, wherein the bilayer consists of an inner layer of palladium or nickel 1 to 30 nm thick and an adjacent outer layer of gold 20 to 200 nm thick.
5. A wire according to any one of claims 1 to 4, exhibiting two or all of said intrinsic properties A1) to A3).
6. 6. A wire according to any one of the preceding claims, wherein the outer layer of gold comprises at least one element selected from the group consisting of antimony, bismuth, arsenic and tellurium in a total proportion in the range of 10 to 300 ppm by weight based on the weight of the wire.
7. 7. The wire of claim 6, wherein the total percentage of the at least one element selected from the group consisting of antimony, bismuth, arsenic, and tellurium is in the range of 300 to 9500 ppm by weight based on the weight of the gold in the outer gold layer.
8. 8. The wire of claim 6 or 7, wherein the at least one element selected from the group consisting of antimony, bismuth, arsenic and tellurium exhibits a concentration gradient within the outer gold layer, the gradient increasing in a direction perpendicular to the longitudinal axis of the wire core.
9. 9. A wire as claimed in claim 6, 7 or 8, wherein antimony is present in the outer layer of gold.
10. 10. The wire of claim 9 wherein antimony is present alone in said outer gold layer without the simultaneous presence of bismuth, arsenic and tellurium.
11. At least steps (1) to (5): (1) preparing a silver-based precursor member; (2) elongating the precursor member until an intermediate diameter in the range of 30 to 200 μm is obtained to form an elongated precursor member; (3) applying a bilayer coating of an inner layer of palladium or nickel and an adjacent outer layer of gold onto the surface of the elongated precursor member obtained after completion of process step (2); (4) further stretching the coated precursor element obtained after completing process step (3) until a desired final diameter is obtained and a bilayer is obtained consisting of an inner layer of palladium or nickel having a desired final thickness in the range of 1 to 100 nm and an adjacent outer layer of gold having a desired final thickness in the range of 1 to 250 nm; (5) Finally, strand annealing the coated precursor obtained after completion of process step (4) at an oven set temperature ranging from greater than 400° C. to 460° C. for an exposure time ranging from 0.8 to 10 seconds to form a coated wire. Including, 11. The method of claim 1, wherein step (2) may include one or more sub-steps of intermediate batch annealing the precursor member at an oven setpoint temperature of 200-650°C for an exposure time in the range of 30-300 minutes.
12. The method of claim 11 , wherein the palladium inner layer or the nickel inner layer is applied by electroplating.
13. 13. The method of claim 11 or 12, wherein the outer gold layer is applied by electroplating.
14. 14. The method of claim 13, wherein applying the outer layer of gold in step (3) is accomplished by electroplating the outer layer of gold from a gold electroplating bath comprising gold and at least one member selected from the group consisting of antimony, bismuth, arsenic, and tellurium.
Citation Information
Patent Citations
Silver wire bonding wire filmed with gold
JP2001176912A
Insulated Wire
JP2019504472A
